Condition Assessment of the Deteriorated Reinforced Concrete Bridge - Gunawan Budi Wijaya; Narciso Pacuribot (Civil Engineering Dimension, 2017)
A comprehensive assessment was conducted to an old reinforced concrete bridge in Brunei Darussalam. This bridge is about 30-40 years old, and has already shown signs of concrete distresses. The main concern was the integrity of the columns, beams and deck, as signs of concrete deteriorations were readily noticeable, e.g. cracks, delaminations, exposed rebar, and concrete spalling. Both visual inspection and non-destructive tests were performed on site. For more detail evaluation, concrete core samples were extracted and sent for testing. Based on information gathered during the investigation and the results of laboratory testing, the reviewed concrete columns were found in bad condition and required immediate repair. The main cause of this concrete distress was the reinforcement corrosion. The vertical column reinforcements were badly corroded and could not function as designed. Without initiating a repair program, it should be prepared for progressive deteriorating conditions, eventually leading to a structural at-risk scenario.